Penggunaan Microscopic Agglutination Test (MAT) dalam Pendiagnosaan Leptospira sp. di Anjing - Erika; Sharon Gunardi; Agus Efendi; Khairiza Asri (Acta VETERINARIA Indonesiana, 2022)
Leptospirosis is an infectious disease that can affect various kinds of animals including dogs and cats. Leptospirosis has a zoonotic potential, therefore it is necessary to confirm a definitive diagnosis in patients suspected infection by leptospirosis. Establishing a diagnosis is important for the public health sector because dogs and cats infected with Leptospira sp. can spread organisms through urine to the environment. Microscopic agglutination test (MAT) is the gold standard for diagnosing leptospirosis. However, MAT has limitations in the sensitivity and specificity of the test because it works by detecting antibodies in the serum. A repeat of the MAT test is necessary to confirm the diagnosis, especially if the antibody titer value is not significantly increased in the first test. Four cases of dogs treated at the Joint Veterinary Practice (PDHB) drh Cucu Kartini Sajuthi with clinical symptoms of jaundice mucous membrane, vomiting, diarrhea, and blood tests showed an increase in blood urea nitrogen and creatinine values ​​indicating impaired kidney function and an increase in serum glutamic pyruvic values transaminase and alkaline phosphatase indicating the impaired of liver cells. The emergence of clinical symptoms and abnormalities in the blood picture led to the suspicion of the patient being infected with Leptospira sp. The MAT test was carried out at the Center for Veterinary Research (BB Litvet) Bogor. The test was repeated with interval of 7-14 days. An increase in antibody titer fourfold or more indicates a strong presence of Leptospira sp. Of the four cases presented, three patients had a 4-fold increase in antibody titer on the second MAT test while one patient did not have an increase in antibody titer. This study concludes that MAT testing is applicable in the clinical diagnosis of leptospirosis, but it is necessary to repeat the test with an interval of 7–14 days.